Knowledge Management for School Education - Cheng, Eric C. K.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
This book introduces the application of knowledge management (KM) theories, practices, and tools in school organization for sustainable development. Schools in Asia Pacific have long faced a variety of challenges in terms of sustainable development under the education reforms and curriculum reforms to meet the demands of a knowledge society. Schools are inevitably expected to develop human capital for the knowledge society within the competitive global economy, and to interact with its policy environment and know how to leverage pedagogical knowledge. The high speed of expansion change and expansion of knowledge have dramatically influence the development of flexibility of teacher and school works. The nature of teacher work becomes increasingly less routine, more analytical, and disruptive yet often come with a sense of urgency and need to be more collaborative. Teachers not only require data and information, but also knowledge and experience of individual, they also need to collaborative task execution, decision making and problem solving. Helping school leaders and teachers to manage their knowledge and become (3z(Bknow how(3y (Bto cope with the change is important.s
Challenges for Schools in a Knowledge Society -- Knowledge Management for School Development -- Managing Culture for Knowledge Management Implementation -- Cultivating Communities of Practice for Leveraging Knowledge -- Nurturing Teachers$1 (BPersonal Knowledge Management Competencies -- Institutionalising a School Knowledge Management System -- A Knowledge Management Model for School Development.s
Keywords: Education; School management and organization; School administration; Teaching; Education; Teaching and Teacher Education; Learning & Instruction; Administration, Organization and Leadership; Electronic books